Morphine Use in ST-Elevation Myocardial Infarction With Downstream P2Y12 Receptor Blockers—Insight From Observational Study. (21st July 2022) - Roguin, Ariel; Kobo, Ofer; Meisel, Simcha Ron; Maraga, Emad; Frimerman, Aaron; Amsalem, Naama; Malka, Rinat; Levi, Yaniv; Fanne, Rami Abu
Background and Aims: Morphine use for patients presenting with NSTE-ACS is associated with excess mortality. However, the role of morphine in STE-ACS is ill characterized. We have recently confirmed direct prothrombotic effect of morphine using murine models. We sought to explore whether morphine use in STE-ACS patients, used to be scheduled for downstream P2 Y12 blockers, is negatively associated with procedural and clinical outcomes. Methods: A single-center, observational retrospective analysis enrolling 130 non-randomized stable patients sustaining STE-ACS as their first manifestation of coronary disease, who presented between December 2010 and June 2013. All were managed by early invasive approach. Of study patients, 55 were treated by morphine, and 75 were not. All were administered downstream P2 Y12 blockers according to an already abandoned local policy. Outcomes evaluated included TIMI grade flow, thrombus burden, ST-segment resolution, myocardial function by echocardiography, and cardiovascular death. Results: Morphine administration was associated with a significantly higher incidence of impaired final TIMI grade flow (TIMI < 3, 40% vs 4%, P < .05), lower incidence of ST-segment resolution >70% (40.7% vs 76.5%, P < .05), and a higher incidence of moderate or severe systolic dysfunction (48.1% vs 29.1%, P < .05) compared with morphine naive patients. Interestingly, the overall mortality rate was higher in the morphine-treated group (18% vs 5.3%, P < .05). Conclusions and Relevance: Morphine administration combined with the downstream P2 Y12 blockers practice signify a group with a higher occurrence of impaired myocardial reperfusion and cardiovascular death despite established on-time primary angioplasty.